2011
DOI: 10.1038/nature10387
|View full text |Cite|
|
Sign up to set email alerts
|

An origin of the radio jet in M87 at the location of the central black hole

Abstract: Powerful radio jets from active galactic nuclei are thought to be powered by the accretion of material onto the supermassive black hole (the 'central engine'). M87 is one of the closest examples of this phenomenon, and the structure of its jet has been probed on a scale of about 100 Schwarzschild radii (R(s), the radius of the event horizon). However, the location of the central black hole relative to the jet base (a bright compact radio 'core') remains elusive. Observations of other jets indicate that the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
354
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(385 citation statements)
references
References 27 publications
(24 reference statements)
29
354
2
Order By: Relevance
“…Because of synchrotron self-absorption, the observed location of the jet core does not correspond exactly to the true base of the jet (Lobanov 1998). However, in the case of M 87, Hada et al (2011) found that the central engine of M 87 and the radio core at 43 GHz are separated by a projected distance of only 41 ± 12 µas, which is small enough to consider, in our case, the core as the point of symmetry of the jet. The counter-jet component which yields a robust speed estimate is located in the northern limb of the counter jet.…”
Section: Counter-jet and Jet Viewing Anglementioning
confidence: 98%
See 1 more Smart Citation
“…Because of synchrotron self-absorption, the observed location of the jet core does not correspond exactly to the true base of the jet (Lobanov 1998). However, in the case of M 87, Hada et al (2011) found that the central engine of M 87 and the radio core at 43 GHz are separated by a projected distance of only 41 ± 12 µas, which is small enough to consider, in our case, the core as the point of symmetry of the jet. The counter-jet component which yields a robust speed estimate is located in the northern limb of the counter jet.…”
Section: Counter-jet and Jet Viewing Anglementioning
confidence: 98%
“…Recently, multi-frequency phase-referencing VLBI observations (Hada et al 2011) were used to locate the central engine at a projected distance of only about 40 R s upstream from the base (or the "core") of the radio jet observed at 43 GHz. Jet expansion can be described with a parabolic profile (Asada & Nakamura 2012), indicating that the jet is collimated by magnetohydrodynamic (MHD) processes (Meier et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The distance z 0 might be a few tens of gravitational radii, 6 based on the fact that the VLBI observation, for instance, of the jet in M87 at 43 GHz gives evidence on the jet collimation (by the toroidal magnetic field) on scales of 60-200 r g (Biretta et al 2002). More recently, Hada et al (2011) argued that 43 GHz VLBI core is located at ∼ 40 r g from the central engine, where they performed the core shift measurement by using multifrequency, phase-referencing Very Long Baseline Array observations, and that the measured frequency dependence of the core shift is in good agreement with a synchrotron self-absorbed jets. The structure of the M 87 jet, from sub-miliarsec to arcsec scales, was also investigated by Nakamura & Asada (2013), where the (bulk) acceleration and collimation of the jet are correlated in a parabolic streamline.…”
Section: Magnetic Field Scaling Along a Steady Jetmentioning
confidence: 99%
“…In this scenarios, we could determine the properties of jet through observing the electromagnetic spectrum. The VLBI images that are observed both at large angles to the jet axis and with a spatial resolution at an order of a parsec (Pearson et al 1996;Zensus 1997;Zensus et al 2006;Lobanov 2010;Kutkin et al 2014), show that there is a continuous axisymmetric plasma jet, which is a approximately conical in geometry ; Kovalev et al 2007) with a small degree of curvature close to the base (Asada & Nakamura 2012) and a blunt base with a wide opening angle (Hada et al 2011). Measuring results of the frequency dependent core-shift are in favour of a conical jet where the magnetic flux conservation is taken into account (Sokolovsky et al 2011).…”
Section: Introductionmentioning
confidence: 99%